CrystalExplorer: a program for Hirshfeld surface analysis, visualization and quantitative analysis of molecular crystals. Issue 3 (2nd May 2021) - Spackman, Peter R.; Turner, Michael J.; McKinnon, Joshua J.; Wolff, Stephen K.; Grimwood, Daniel J.; Jayatilaka, Dylan; Spackman, Mark A.
Abstract : CrystalExplorer is a native cross‐platform program for the visualization and investigation of molecular crystal structures. Abstract : CrystalExplorer is a native cross‐platform program supported on Windows, MacOS and Linux with the primary function of visualization and investigation of molecular crystal structures, especially through the decorated Hirshfeld surface and its corresponding two‐dimensional fingerprint, and through the visualization of void spaces in the crystal via isosurfaces of the promolecule electron density. Over the past decade, significant changes and enhancements have been incorporated into the program, such as the capacity to accurately and quickly calculate and visualize quantitative intermolecular interactions and, perhaps most importantly, the ability to interface with the Gaussian and NWChem programs to calculate quantum‐mechanical properties of molecules. The current version, CrystalExplorer21, incorporates these and other changes, and the software can be downloaded and used free of charge for academic research.